Clinical Profile of Acute Myeloid Leukemia in North India and Utility of Nontransplant Measures in its Management - Shoket, Nadeem; Muzamil, Javvid; Zargar, Tasneef Banoo; Wani, Burhan; Toka, Vishal; Bhat, Javid Rasool; Bhat, Gull Mohammad; Shiekh, Aejaz Aziz (Indian Journal of Medical and Paediatric Oncology, 2019)
Introduction: Acute myeloid leukemia (AML) is a clonal accumulation of myeloid precursors in body tissues, which ultimately leads to bone marrow failure. This is an 8-year prospective, observational study in which 254 patients were enrolled. Aim of the Study: To document the clinical profile of AML and differential outcome in M3 versus non-M3 phenotype and to see impact of different variables on its survival. Methods: Patients enrolled in the study were examined, evaluated, and given standard 3:7 induction protocol, and acute promyelocytic leukemia (APML) patients were given the ICAPL 2006 protocol. Results: In our study, males outnumbered females and most of our patients were in 20–60 years of age group. The better prognosis was in patients who were in the second decade of life. Total leukocyte count and platelet count had a significant impact on the survival of the a patient. Bone marrow morphology of M3 type has extremely good prognosis and was the most common FAB type seen in our study. Flow cytometric markers such as CD15, CD33, CD117, and myeloperoxidase had positivity among 90% of patients. Overall survival is around 40% in whole-study group, 87% in APML group, and 16.5% in non-M3 group. There are still unmet needs in managing the non-M3 patients in resource-constraint countries where allogenic transplant and newer drugs have the least access. For improving the outcome in M3 AML, further newer molecules such as Flt3 and PIK3 inhibitors are being used in trials. Conclusion: There are still unmet needs in managing the non-M3 patients in resource-constraint countries where allogenic transplant and newer drugs have the least access. For improving the outcome in M3 AML, further newer molecules such as Flt3 and PIK3 inhibitors are being used in trials.
Keywords: Acute myeloid leukemia; acute promyelocytic leukemia; cluster differentiation; event-free survival; myelodysplastic leukemia; myeloperoxidase; overall survival; reverse-transcriptase polymerase chain reaction; total leukocyte count